Media Image of Former Olympian. Renata Mauer-Różańska Case Study - Cięszczyk, Ilona (Journal of Education, Health and Sport, 2019)
This paper tackles the issue of image, with an emphasis on personal image (personal PR). Image was selected as the focal point of this article as, according to the author, it is an indispensable element of media life and functioning in the society. There are numerous definitions of image in both Polish and foreign literature. In his or her definition, each author attempts to incorporate the aspects most important to the world of business and its actors. This paper is centered on distinguishing between such concepts as image, reputation and identity, as well as portrays the evolution of image in time and growing social awareness of the notion, and presents the methodology of building image. This study aims to determine the image of Renata Małgorzata Mauer-Różańsk as it is presented in the national press. The articles referencing the former Olympian analyzed herein were sourced from three nationwide dailies: Fakt, Gazeta Wyborcza and Super Express. The entire material collected and analyses allow to conclude that Renata Małgorzata Mauer-Różańska has a moderately positive image. On the one hand, she is viewed as an authority figure and a walking icon and, on the other, as a person who is withdrawn, afraid to step out of her comfort zone and avoids social media, as well as industry events.